La composizione di ‘Camma’ nel carteggio tra Adelaide Ristori, Giuseppe Montanelli e Lauretta Cipriani Parra - Giacomo Della Ferrera (Drammaturgia)
Among Adelaide Ristori’s great successes, Camma, premiered in Paris on April 23rd, 1857, was written for her by Giuseppe Montanelli. From the perspective of a dramaturgical investigation into how a Grande Attrice chose and construct her repertoire, the correspondence between Montanelli and Ristori is an important case study: the author sends the various acts of the tragedy, as they were completed, to the actress, who gradually comments on their value and offers suggestions for their better stage success, well aware of the strategies to best enhance her own abilities and the expectations of the audience. Ristori’s answers, always lucid, focused and decisive, allow us to recognize to what extent a Grande Attrice would intervene on a text, tailor-made for her, considering her strengths and abilities. Thus, this essay is about the compositional strategies of the textual score and is based on an in-depth reading of the correspondence, investigated especially with regard to the actress’s interventions, whose actual realisation and success are then compared with the final script and the review of the tragedy’s outcome with audiences and critics.